The Role of the Wedding Ceremony in Hellenistic Macedonia - Nataliya Y. Sivkina (Publishing house "Sreda", 2022)
The history of the Hellenistic kingdoms remains the subject of many scientific discussions. The question of the peculiarities of the Macedonian monarchy has been widely discussed again in recent years. To solve this problem, they study certain aspects of the political, social and cultural life of the state, which confirms the relevance of the chosen topic. The purpose of this study is to identify the role of the royal wedding ceremony in the politics of the Macedonian rulers. The research is based on narrative and epigraphic sources. The main methods are analysis and synthesis, as well as comparative-historical. The celebration of the royal wedding is designed to demonstrate the power of the dynasty and seal the political union of the two states. However, with regard to Hellenistic Macedonia, these statements should be considered in the context of the reign of Philip II. Although narrative sources have preserved little information, but their comparison allows us to assert that the beginning of such luxurious events was laid by Philip II. At the same time, his own weddings, apparently, were limited to a feast and did not serve as a guarantor of peace and the union of the two states. The changes took place at the wedding of his daughter Cleopatra. Probably, the changes are connected with the new status of the king himself, who became the head of the Corinthian League. Since that time, the marriage ceremonies of the Hellenistic kings have been held on the same scale. Conclusions. In fact, Philip has established a new tradition. Marriage was not a guarantee of non-aggression of new relatives against each other. The pomp of the ceremony, on the one hand, was a demonstration of the power and authority of the dynasty, and on the other hand, it was used to promote a particular political idea.